Triphenylamine–benzimidazole based switch offers reliable detection of organophosphorus nerve agent (DCP) both in solution and gaseous state. (28th September 2017) - Aich, Krishnendu; Das, Sangita; Gharami, Saswati; Patra, Lakshman; Kumar Mondal, Tapan
Abstract : Triphenylamine-conjugated imidazole dye acts as a potential sensor for the liquid and vapour phase detection of nerve agent simulantDCP . Abstract : In this study, a triphenylamine–benzimidazole (TPIM )-functionalised switch has been fabricated for ratiometric recognition of organophosphorus (OP) chemical vapor. Interestingly, upon addition of the nerve agent mimic diethyl chlorophosphate (DCP ), a prominent color change from colorless to yellow along with a fluorescence color change from cyan to deep yellow was noticed. The chemodosimeter (TPIM ) undergoes tandem nucleophilic substitution reaction withDCP and shows a specific colorimetric and fluorescence alteration. The probe selectively detectsDCP over other toxic substituents studied. In addition, the detection limit ofTPIM forDCP was found to be in the order of 10 −8 M in solution phase using fluorescence method. We have also developed a transportable kit forDCP using our probe (TPIM ), which can detectDCP vapour with high sensitivity.